A Comparative Study of Tamil and English Proverbs - Perumal, V. (Journal of Information and Knowledge, 1984)
Discusses the information contents and style of presentation of ideas contained in the Tamil proverbs and the parallel English proverbs. Compares the proverbs in both the languages and brings out the socio-cultural aspects depicted in them.